Socio-Cultural Globalization and Its Relevance to The Labuhan Merapi Tradition as a Multicultural Educational Space for The Community - Wildhan Ichzha Maulana; Djono Djono; Yusuf Budi Prasetya Santosa; Maulana Yusuf Arrasuly; Roro Wilis (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
The massive flow of socio-cultural globalization today poses a challenge of cultural homogenization, which has the potential to cause deculturalization and an identity crisis in society. However, socio-cultural globalization also presents benefits that can support the preservation and optimization of local wisdom. The purpose of this research is to analyze and describe socio-cultural globalization and its relevance to the Labuhan Merapi tradition as a multicultural educational space for society. This research employs a qualitative approach with a library research method to identify and analyze various relevant literature on globalization, Labuhan Merapi, and multicultural education. Next, data analysis is carried out using the Klaus Krippendorff analysis model, and its credibility is strengthened through source triangulation. The results of the research indicate that socio-cultural globalization has encouraged the